Production and Biological Activity of Monoterpenes from Flowers and Callus Cultures of Michelia Alba Dc. - Rusdi, Nor Azizun (2005)
Analysis of volatile compounds from the selected flower buds, grown in -vitro and caUus cultures of Michelia alba D.C were performed using the gas chromatography technique with mass spectrometry detector (GC-MS). The results showed that the major volatile compound obtained from the three-selected tlower bud was dihydrocarveol. Petal grown in-vitro on the Murashige and Skoog (MS) basal medimn with different concentrations of plant growth regulators did not produce any dihydrocarveol. But callus grown in the culture medium containing 1.25 mgIL (w/v) ofNAA plus 1.35 mgIL (w/v) ofBAP (T20) and 0.8 mgIL (w/v) ofNAA plus 1.85 mgIL of BAP (T23) produced linalool as a major compounds. On the other hand, callus treated with 1.25 mgIL (w/v) ofNAA plus 0.45 mgIL (w/v) ofBAP (TIO) and T20 (1.25 mgIL (w/v) of NAA plus 1.35 mgIL (w/v) of BAP were able to synthesis cyclohexane (32.96±1.94%) compared to T23 (17.015±1.06%). Callus derived from flower petal of M alba treated with 1.25 mgIL (w/v) ofNAA plus 0.45 mgIL (w/v) of BAP (TlO) gave the higher growth (23.83±1.44 g F.wtI culture; 0.23±0.09 g D.wtlculture) respectively at pH 5.7, 25±2°C and in the complete dark condition after 5 weeks of culture. Treatment of M alba flower petal derived callus with 1.0 mgIL (w/v) NAA plus 1.0 mgIL (w/v) BAP supplied with 150 mgIL (w/v) of casein hydrolysate showed higher growth (0.211±0.02 g D.wtI culture) than all other concentrations of casein hydrolysate. Most of the new volatile compounds in the callus cultures were found after treatment with 150 mgIL (w/v) of casein hydrolysate. Addition of various concentrations of bioelicitors, jasmonic acid (0 to 0.25 mglmL (w/v) yeast extract (0-0.3% (w/v» and pectinase (0-0.25 mglmL (w/v» into the culture medium, decreased the cell growth. However, treatment of flower petal derived callus with (0.25 mglmL (w/v» of pectinase showed the highest growth (0.1l8±0.002 g D.wtlculture) on day 18th compared to other treatment. On the other hand, petal derived callus treated with jasmonic acid and L-phenylalanine decreased the callus growth but significantly increased the production of new volatile compounds i.e. cinnamaldehyde, caryophyllene, nerolidol, cinnamic acid, ocimene, famasene, undecene, germacrene D and also linalool. The essential oils obtained from flower bud showed the insecticidal activities, against Tribolium castaneum adults. The insecticidal property of essential oil obtained from flower and petalderived callus was probably associated with presence of linalool, eugenol and geraniol. Result from seed germination assay also showed that pentane extract of Michelia alba flowers was able to effect the germination of the Brassica nigra L (mustard seeds) tested. The phytotoxicity effect and cytotoxicity action may also be possibly associated with the presence of cineol, limonene and linalool though they are minor components.